2003
DOI: 10.1039/b302429f
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced electron transfer at solid surfaces: the TiO2–SiO2 system

Abstract: Small particles of TiO2 have been synthesized on porous silica. XRD and spectral measurements place the sizes of the particles at about 50 A. With these small particles the band gap of the semiconductor material is markedly blue shifted with respect to bulk TiO2. This enables the direct excitation of co-adsorbed arenes on the TiO2-SiO2 material. Direct excitation of TiO2 leads to Ti3+, by photoinduced extraction from the SiO2. Direct excitation of pyrene on the material leads to a shortened fluorescence lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This type can be obtained by the preparation of TiO 2 -SiO 2 catalyst with the electron transfer across the solid-solid TiO 2 -SiO 2 interface. For that reasons, in a previous study it was reported that the TiO 2 -SiO 2 catalyst is 3 times more photoactive than TiO 2 alone [10][11][12]. Another possibility is to modify TiO 2 by surface deposition of noble metals to shift the process of photodegradation of organic pollutants into the visible-light region [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This type can be obtained by the preparation of TiO 2 -SiO 2 catalyst with the electron transfer across the solid-solid TiO 2 -SiO 2 interface. For that reasons, in a previous study it was reported that the TiO 2 -SiO 2 catalyst is 3 times more photoactive than TiO 2 alone [10][11][12]. Another possibility is to modify TiO 2 by surface deposition of noble metals to shift the process of photodegradation of organic pollutants into the visible-light region [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of SiO 2 in TiO 2 nanoparticle photocatalysts is able to increase the surface acidity [10], to increase the active surface area [14], to promote the adsorption of organic compounds [15], to help the electron transfer [16], and to modify the band gap [17], leading to enhanced PC decomposition of organic pollutants [18][19][20]. It is possible to increase the PC and PEC activity of TiO 2 films by introducing SiO 2 into the film.…”
Section: Introductionmentioning
confidence: 99%
“…This type can be obtained by the preparation of TiO 2 -SiO 2 catalyst with the electron transfer across the solid-solid TiO 2 -SiO 2 interface. It was previously reported that the catalytic activity of TiO 2 -SiO 2 is 3-fold higher than corresponding TiO 2 (Anderson and Bard, 1995;Ruetten and Thomas, 2003;Chun et al, 2001). Another possibility is to modify TiO 2 by surface deposition of noble metals to shift the process of photodegradation of organic pollutants into the visible-light region (Wang et al, 1998;Yang et al, 1997;Kisch et al, 1998;Li and Li, 2002).…”
Section: Introductionmentioning
confidence: 93%